2023
DOI: 10.3390/ani14010112
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Gut Microbiota Associated with Parity in Large White Sows

Yage Bu,
Lingli Feng,
Di Xu
et al.

Abstract: As one of the most critical economic traits, the litter performance of sows is influenced by their parity. Some studies have indicated a connection between the gut microbiota and the litter performance of animals. In this study, we examined litter performance in 1363 records of different parities of Large White sows. We observed a marked decline in TNB (Total Number Born) and NBH (Number of Healthy Born) We observed a marked decline in TNB (Total Number Born) and NBH (Number of Healthy Born) among sows with pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…In sows, it identified that parity as an important environmental factor that modulates the gut microbiome, and that potential pathogenic bacteria become increasingly enriched with increasing parity [22]. Similarly, higher parities are linked with increased risks of individual mortality, the number of piglets born alive, and the number of piglets born weaned compared to lower parities [23].…”
Section: Introductionmentioning
confidence: 99%
“…In sows, it identified that parity as an important environmental factor that modulates the gut microbiome, and that potential pathogenic bacteria become increasingly enriched with increasing parity [22]. Similarly, higher parities are linked with increased risks of individual mortality, the number of piglets born alive, and the number of piglets born weaned compared to lower parities [23].…”
Section: Introductionmentioning
confidence: 99%